550 Hospital Frailty Risk Score is an Independent Risk Factor for VP Shunt Placement for Ruptured Intracranial Aneurysms. (April 2023) - Koo, Andrew B.; Elsamadicy, Aladine A.; Sarkozy, Margot; Reeves, Benjamin; Craft, Samuel; Sherman, Josiah; Sayeed, Sumaiya; Antonios, Joseph Paul; Renedo, Daniela; Sujijantarat, Nanthiya; Hebert, Ryan Matthew; Malhotra, Ajay; et al.
Abstract : INTRODUCTION: Frailty is an important predictor of poor surgical outcomes. Identifying patients who will require ventriculoperitoneal (VP) shunt placement following endovascular management for ruptured intracranial aneurysms (IA) remains poorly understood. METHODS: A retrospective study of the National Inpatient Sample database (2016-2019) was performed. Patients ≥18 years old undergoing endovascular treatment for IA after subarachnoid hemorrhage identified using ICD-10-CM coding were dichotomized by whether they underwent VP shunt placement during the index admission. Only patients with coding for initial external ventricular drain placement were included. Demographics, comorbidities, adverse events (AEs), LOS, discharge disposition and total cost were assessed. A multivariate analysis was used to assess the influence of HFRS on VP shunt placement. RESULTS: Of the 12, 935 patients identified, 2, 805 (21.7%) required VP shunt placement. The shunt population was older (No Shunt: 56.6 ± 13.5 years vs. Shunt: 58.5 ± 12.6 years, p = 0.002). HFRS-defined frailty was greater in the shunted population (No Shunt: 11.1±5.4 vs Shunt: 12.3 ± 5.5, p<0.001). The shunted population experienced more AEs (No Shunt: 83.2% vs. Shunt: 89.5%, p < 0.001). Mean LOS (No Shunt: 23.0 ± 13.6 days vs Shunt: 31.7 ± 18.9 days, p<0.001), mean cost (No Shunt: $115, 808 ±64, 428 vs Shunt: $160, 024 ± 92, 014, p < 0.001), and non-routine discharge (No Shunt: 64.5% vs Shunt: 79.9%, p < 0.001) were greater in patients shunted. On multivariate analysis, several risk-factors were associated with VP shunt placement, including frailty, age, female sex, hydrocephalus, dysphagia, pulmonary circulation disorders, other neurological disorders, and aneurysm location. The odds ratio for Frailty was 1.53 (p = 0.025) for intermediate-frailty patients and 1.69 (p=0.011) for high-frailty patients compared to low-frailty patients. CONCLUSIONS: Our study demonstrates that HFRS is an independent predictor of VP shunt placement following endovascular treatment of ruptured intracranial aneurysms.